Pengaruh Store Atmosphere, dan Promosi serta Kualitas Pelayanan terhadap Kepuasan Pelanggan Pada Coffee Shop - Nursalmah, Vicky Yasmin; Sahir, Syafrida Hafni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of coffee shops is quite rapid in the city of Medan. However, the satisfaction of coffee lovers has not been as expected, allegedly due to the unattractive atmosphere of the place, ineffective promotion and slow service. The purpose of the study was to determine the effect of store atmosphere, promotion and service quality on customer satisfaction at the coffee shop minum dulu halat Kec. Medan Area. The type of quantitative descriptive research with a case study. The population is 1200 coffee shop customers in 1 month and the number of samples is 93 people. The analysis technique uses a statistical model consisting of validity, reliability, classical assumptions, multiple linear regression, t-test, F-test and coefficient of determination (R2) using SPSS (Statistical Product and Service Solutions) software version 26. Data sourced from primary data and the data collection process using a questionnaire. The results of the study showed that partially there is an influence of store atmosphere, promotion, and service quality on customer satisfaction with each t-value (2.044, 2.828, 3.085) greater than t-table (1.987) and a significance level (0.044, 0.006, 0.003) smaller than 0.05. The F-value obtained > F-table (40.763> 2.710) with a significance level (0.000 <0.05), so the hypothesis is accepted, partially and simultaneously store atmosphere, promotion, and service quality have a positive and significant effect on customer satisfaction.